2019
DOI: 10.1016/j.bja.2019.04.057
|View full text |Cite
|
Sign up to set email alerts
|

Propofol-based total intravenous anaesthesia is associated with better survival than desflurane anaesthesia in hepatectomy for hepatocellular carcinoma: a retrospective cohort study

Abstract: Background: Previous studies have shown that anaesthetic technique can affect outcomes of cancer surgery. We investigated the association between anaesthetic technique and patient outcomes after elective hepatectomy for hepatocellular carcinoma. Methods: This was a retrospective single-centre cohort study of patients who received elective hepatectomy for hepatocellular carcinoma from January 2005 to December 2014. Patients were grouped according to propofol or desflurane anaesthesia. KaplaneMeier analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 41 publications
(25 reference statements)
6
84
2
Order By: Relevance
“…Apart from its anesthetic effects, propofol also exerts a number of non-anesthetic effects, such as reduction of oxidative damage [37], decreases proinflammatory cytokines [38], inhibits COX-2 and PGE 2 functions and decrease surgery-induced neuroendocrine responses and cause less immunosuppression and recurrence of certain types of cancer [39,40]. In vitro and in vivo, propofol could inhibit invasion, migration, metastasis and induced apoptosis and cell cycle arrest of numerous cancer cells [12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from its anesthetic effects, propofol also exerts a number of non-anesthetic effects, such as reduction of oxidative damage [37], decreases proinflammatory cytokines [38], inhibits COX-2 and PGE 2 functions and decrease surgery-induced neuroendocrine responses and cause less immunosuppression and recurrence of certain types of cancer [39,40]. In vitro and in vivo, propofol could inhibit invasion, migration, metastasis and induced apoptosis and cell cycle arrest of numerous cancer cells [12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…The results were consistent with our previous reports demonstrating that propofol anesthesia was related to better survival and a lower incidence of postoperative recurrence or metastasis compared with desflurane anesthesia in colon cancer, hepatocellular carcinoma, and intrahepatic cholangiocarcinoma surgery. [15,16,20,21] By contrast, there were retrospective studies reporting insignificant differences in overall survival between the use propofol and VAs in surgery for breast cancer, lung cancer. [11,22,23] To our best knowledge, there are very few researches of the effects of the propofol and VAs in patients undergoing prostate cancer surgery, and further investigations are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Repetitive bolus injections of fentanyl and cisatracurium or rocuronium were used as needed during surgery. [15,16] Desflurane or maintenance of the effect-site concentration with target-controlled infusion using propofol was adjusted downward and upward by 0.5-2% or 0.2-0.5 μg/mL, respectively, when needed based on the hemodynamics. The level of end-tidal carbon dioxide was kept at 35-45 mmHg by adjusting the ventilation rate with volume control model with tidal volume 6-8 mg/kg and kept a maximum airway pressure < 30 cm H 2 O.…”
Section: Participants and Data Sourcesmentioning
confidence: 99%
“…50 Similarly, a retrospective cohort study uncovered that patients in desflurane anesthesia group had a worse outcome, such as higher mortality rate (75.0% versus 30.8%), distant metastasis (15.9% versus 5.5%) or a higher local recurrence (70.1% versus 37.8%), compared with propofol group in HCC patients who underwent hepatectomy during 10 years' follow-up. 51 In contrast, a clinical research found that epithelial ovarian cancer patients at stage III who were given desflurane were related to a less overall rate of recurrence during primary cytoreductive surgery compared with patients who were given sevoflurane. 52 But the Kaplan-Meier curves demonstrated that PFS and OS rates at 1 and 5 years were similar for patients given desflurane in comparison with isoflurane during the glioblastoma surgery.…”
Section: Vegf and Angiopoietin-1mentioning
confidence: 96%